2017
DOI: 10.1155/2017/3459785
|View full text |Cite
|
Sign up to set email alerts
|

Infections Caused by HRSV A ON1 Are Predominant among Hospitalized Infants with Bronchiolitis in São Paulo City

Abstract: Human respiratory syncytial virus is the main cause of respiratory infections in infants. Several HRSV genotypes have been described. Goals. To describe the main genotypes that caused infections in São Paulo (2013–2015) and to analyze their clinical/epidemiological features. Methods. 94 infants (0–6 months) with bronchiolitis were studied. Clinical/epidemiological information was collected; a search for 16 viruses in nasopharyngeal secretion (PCR-real-time and conventional, sequencing, and phylogenetic analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
2
8
0
2
Order By: Relevance
“…In our study, the median age of four months in hospitalized children with RSV confirms the higher prevalence in children younger than one year of age [ 2 ], which justifies why RSV vaccine candidates are aiming to protect, primarily, infants and young children [ 7 ]. Although the median hospitalization length of stay found here is similar to some other studies [ 27 , 28 ], notably, most of them report a shorter duration [ 1 , 4 , 25 ]. One hypothesis that could explain this finding is the fact that all children included in our study were diagnosed with SARI, which makes our study group a cohort with severe RSV infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the median age of four months in hospitalized children with RSV confirms the higher prevalence in children younger than one year of age [ 2 ], which justifies why RSV vaccine candidates are aiming to protect, primarily, infants and young children [ 7 ]. Although the median hospitalization length of stay found here is similar to some other studies [ 27 , 28 ], notably, most of them report a shorter duration [ 1 , 4 , 25 ]. One hypothesis that could explain this finding is the fact that all children included in our study were diagnosed with SARI, which makes our study group a cohort with severe RSV infection.…”
Section: Discussionsupporting
confidence: 89%
“…RSV prevalence in different Brazilian regions is highly diverse, ranging from 7.7% to 77.6% [24][25][26]. In the ES state, from 2016 to 2018, the prevalence in hospitalized children up to 3 years of age was 56%.…”
Section: Rsv Is Prevalent In Brazilian Children With Sarimentioning
confidence: 99%
“…A possible association between RSV subtypes and disease severity has been investigated; the interest was renewed since the identification of the ON1 genotype, but it was concluded that it is not associated with disease severity [10,18]. This is in accordance with the results of the current study, since none of the RSV ON1-infected patients required mechanical ventilation or admission to intensive care, and no relation was observed between subtype and disease severity.…”
Section: Jn257693 Q E E T L H S T T S E G Y L S P S Q V Y T T S G Q Esupporting
confidence: 88%
“…We also used this definition in this study and the p-distance showed that NA1 and ON1 could be classified into a single clade (p-distance, 0.039). However, we retained NA1 and ON1 as independent clades in this study to keep consistency from the previous reports by the reason for an unique 72 nucleotide duplication observed in ON1 [ 12 , 37 , 54 , 56 60 ].…”
Section: Discussionmentioning
confidence: 91%